Cross-border labor market participation in the Greater Region for young people - challenges for social work(ers) - Ulrike Zöller (Social Work and Society)
This contribution provides an overview of cross-border work mobility in the Greater Region (including areas of Germany, Luxembourg, and Belgium) in the vocational education and training of young people. Increased mobility is expected in modern working life and is a focus of social work stakeholders in the Greater Region. Cross-border work mobility in vocational education and training provides additional opportunities for young people, and the field of social work has addressed this challenge. Reviewing current practices, it is evident that despite the initial efforts to promote work mobility for young people in the Greater Region, youths from sociodemographically disadvantaged backgrounds hardly benefit from them. Yet youth vocational assistance (Jugendberufshilfe)[1] could play a larger role to promote cross-border occupational mobility thus contributing to the reduction of social disadvantages in youths. After describing the current sociostructural situation in the Greater Region, a summary of the mobility opportunities created for young people to date is provided and the challenges facing youth vocational assistance services in the Greater Region to successfully advance the cross-border mobility of young people are discussed. These considerations focus on how"mobility as an opportunity for vocational integration" (Dreizehn 2018, Issue 20) can be accomplished for young people in the Greater Region and on the role of youth vocational assistance in achieving this goal.